PENGEMBANGAN SISTEM INFORMASI MANAJEMEN LABORATORIUM KOMPUTER UNTUK MENDUKUNG PROSES ADMINISTRASI BEBASIS WEB - Wulan Andang Purnomo; Dwi Winarti; Yusran Yusran (Politeknik Bisnis Indonesia, 2022)
The Faculty of Computer Science, Dharmas University Indonesia must have adequate laboratory facilities, this is because the Departments in the Faculty of Computer Science are 60% practice and 40% theory. Currently the facilities owned by this Faculty are quite adequate but administratively they are still not supportive. One of them is the process of borrowing computers, scheduling practices, and processing Inventory data which is still conventional, which is done by recording on a ledger and a piece of paper. If this continues, it is likely that data will easily be lost in the administration of documents and goods data that is not neat. In addition, officers will find it difficult to determine the scheduling of practicum courses. To solve these problems, a web-based laboratory Management Information System was designed to make it easier for workforce officers and lecturers to carry out learning activities and borrow practicum tools. The Waterfall method is used to build this system. The results of the research are web products built using PHP MySQL. Through this system the performance of officers is increasing because officers can manage inventory data, information on incoming and outgoing goods, scheduling courses, borrowing computer workforce facilities easily and quickly.